2019
DOI: 10.3389/fmicb.2019.02124
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Colonization of Broiler Chickens With ESBL-/AmpC- Producing Escherichia coli in a Seeder-Bird Model Independent of Antimicrobial Selection Pressure

Abstract: Extended-spectrum beta-lactamase- (ESBL-) and AmpC beta-lactamase- (AmpC-) producing Enterobacteriaceae pose a risk for both human and animal health. For livestock, highest prevalences have been reported in broiler chickens, which are therefore considered as a reservoir of multidrug-resistant bacteria. The possibility of transfer to humans either by a close contact to colonized broiler flocks or through contaminated retail meat results in the necessity to develop intervention measures for the entire broiler pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Before the trial, the absence of ESBL- and pAmpC- producing bacteria was confirmed in the eggshells and in the one-day-old broiler chickens as well as in the experimental room and on the equipment as described in our seeder-bird colonization model [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Before the trial, the absence of ESBL- and pAmpC- producing bacteria was confirmed in the eggshells and in the one-day-old broiler chickens as well as in the experimental room and on the equipment as described in our seeder-bird colonization model [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…coli strain (CMY-2, mcr-1; ST10; phylogenetic group A; internal number 10717). Both strains were isolated in a previous research project [ 23 ] and were recently used to establish our seeder-bird colonization model [ 12 ]. In this colonization model, both commensal E .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations